Are patients' goals in treatment associated with expected treatment outcomes? Findings from a mixed-methods study on outpatient pharmacological treatment for opioid use disorder. Issue 1 (12th January 2021) - Rosic, Tea; Naji, Leen; Panesar, Balpreet; Chai, Darren B; Sanger, Nitika; Dennis, Brittany B; Marsh, David C; Rieb, Launette; Worster, Andrew; Thabane, Lehana; Samaan, Zainab
Abstract : Objectives: Existing methods of measuring effectiveness of pharmacological treatment for opioid use disorder (OUD) are highly variable. Therefore, understanding patients' treatment goals is an integral part of patient-centred care. Our objective is to explore whether patients' treatment goals align with a frequently used clinical outcome, opioid abstinence. Design: Triangulation mixed-methods design. Setting and participants: We collected prospective data from 2030 participants who were receiving methadone or buprenorphine-naloxone treatment for a diagnosis of OUD in order to meet study inclusion criteria. Participants were recruited from 45 centrally-managed outpatient opioid agonist therapy clinics in Ontario, Canada. At study entry, we asked, 'What are your goals in treatment?' and used NVivo software to identify common themes. Primary outcome measure: Urine drug screens (UDS) were collected for 3 months post-study enrolment in order to identify abstinence versus ongoing opioid use (mean number of UDS over 3 months=12.6, SD=5.3). We used logistic regression to examine the association between treatment goals and opioid abstinence. Results: Participants had a mean age of 39.2 years (SD=10.7), 44% were women and median duration in treatment was 2.6 years (IQR 5.2). Six overarching goals were identified from patient responses, including 'stop or taper off of treatment' (68%), 'stay or get clean' (37%) and 'live a normal life' (14%). Participants reporting the goal 'stay or get clean' had lower odds of abstinence at 3 months than those who did not report this goal (OR=0.73, 95% CI 0.59 to 0.91, p=0.005). Although the majority of patients wanted to taper off or stop medication, this goal was not associated with opioid abstinence, nor were any of their other goals. Conclusions: Patient goals in OUD treatment do not appear to be associated with programme measures of outcome (ie, abstinence from opioids). Future studies are needed to examine outcomes related to patient-reported treatment goals found in our study; pain management, employment, and stopping/tapering treatment should all be explored.